HPV Vaccine Optimization Concerning Cervical Cancer - Yan, Yan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cervical cancer, associated with human papillomavirus (HPV), is currently the fourth most prevalent cancer among women in the world. Though nowadays there are HPV vaccines available on the market, more strategies need to be taken to improve them and develop more therapeutic vaccines. Recent research has mostly concentrated on the state of HPV vaccinations, including their mechanisms, clinical efficacy, and room for improvement. However, there is a significant research deficit in the field of therapeutic HPV vaccination development. This paper analyzes the mechanisms of both prophylactic and therapeutic HPV vaccines, analyzes the clinical efficacy of five major vaccines in China, and discusses strategies for optimizing HPV vaccines through adjuvants and targeted antigen design. This thorough analysis offers insightful perspectives on the efficacy and safety of the HPV vaccine and makes recommendations for further study and immunization campaigns. However, the problems about the impact of vaccination programs and HPV-related diseases in men haven’t been solved yet. Therefore, future studies should target developing therapeutic HPV vaccines, improving HPV vaccines in the next generation, increasing the awareness of the public, and increasing accessibility of vaccines to release the burden of cervical cancer globally.